Acute effect of different orders of concurrent training on glycemia - Osvaldo Tadeu da Silva Junior; Gustavo Marinho do Nascimento; Giovane Henrique da Silva Nishioka; Anderson Polesel Batista; Jose Alexandre Curiacos; Julio Wilson dos Santos (Bioscience Journal, 2021)
The present study verified the effect of a concurrent training (CT) session in different orders, Strength + Endurance (SE) and Endurance + Strength (ES), on the glycemic control. The crossover study included 20 young men, 21.80 ± 2.90 years, IMC ≥ 23 kg/m2, 24.83 ± 3.68% of fat, who performed both CT sessions separated by 72 h. Capillary glycemia was measured at pre, immediately post the end of each exercise session, and during the recovery period at 30, 60, and 90 minutes. The comparisons were performed using Two-way ANOVA (order and time), paired test-t for the area under the curve, as well as Cohen’s d effect size. There was effect of exercise order (F = 5.973; p = 0.03), effect of time (F = 18.345; p = 0.001) and interaction between order and time (F = 2.835; p = 0.03). The area under the curve presented a significant reduction (p = 0.03, effect size = 0.51, moderate). The area under the curve was smaller in SE, as well as glucose concentrations at end and post 30 min of exercise, suggesting better efficiency in glycemic control compared to ES.